Reinventing Masculinity : the Liberating Power of Compassion and Connection. - Adams, Ed (Berrett-Koehler Publishers, Incorporated, 2020)
"In the wake of the #MeToo movement, a leading psychologist and a top journalist offer an alternative to toxic masculinity that is rooted in compassion, connection and respect"--